Conversations with marketing masters - Mazur, Laura; Miles, Louella (Chichester ; Hoboken, NJ : John Wiley, 2007)
Conversations with Marketing Masters offers new insights by gathering the collected wisdom of the most influential marketing thinkers of our age, each of whom has given a structured interview. Covering a wide range of issues and illustrating concepts with cases of success and failure, these seminal dialogues offer a rare look at what made each master great - and a glimpse of the marketing future.
Philip Kotler : the founding father -- David Aaker : brand equity trailblazer -- Jean-Claude Larreche : marketing strategy master -- Regis Mckenna : the technology visionary -- Don Peppers and Martha Rogers : one-to-one gurus -- John Quelch : global marketing authority -- Al Ries : pioneer of positioning -- Don Schultz : integrated marketing communications innovator -- Patricia Seybold : customer experience expert -- Jack Trout : positioning pioneer -- Lester Wunderman : direct marketing missionary.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Marketing; Marketing -- Management; Marketing personnel -- Interviews; Marketing; Marketing; Marketing -- Gestion; Marketing -- Personnel -- Entretiens; marketing; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Distribution; Marketing; Marketing -- Management; Marketing personnel; Marketing; 2; Arbeitskraft; Marketing; Management; Marketing; Marketing -- Management; Marketing personnel -- Interviews; Marketing; Marketing -- Management; Marketing personnel -- Interviews; 2; MARKETING; Interviews; interviews; Interviews; Interviews